The rediscovery of the limit as an ethical path to the discussion on abortion - Iacone, Ignazio (Medicina e Morale, 2023)
The June 2022 US Supreme Court ruling on abortion was read by many pro-choice political bodies and associations as a step backwards in the path of civil rights, Neglecting its dangerous ethical implications in the opposite direction and confirming an idea of pregnancy difficult as a problem to be eliminated and not as an opportunity to be protected. Both the American case and the Italian debate on Law 194 call into question the philosophical concept of the limit, whose value for human knowledge should be rediscovered, as Kant first declared. Those who stand up for life, and among them the Church, demand policies that can protect both the mother and the son, and at the same time conscientious objectors. Ethics has the task of seeking ways of truly open dialogue, in the direction of a truth that transcends the diversity of opinions and cultures and guides humanity in the progress towards Good.